An HIT Solution for Clinical Care and Disaster Planning: How One health Center in Joplin, MO Survived a Tornado and Avoided a Health Information Disaster - Shin, Peter (University of Illinois at Chicago Library, 2012)
Since taking office, President Obama has made substantial investments in promoting the diffusion of health information technology (IT). The objective of the national health IT program is, generally, to enable health care providers to better manage patient care through secure use and sharing of health information. Through the use of technologies including electronic health records, providers can better maintain patient care information and facilitate communication, often improving care outcomes. The recent tornado in Joplin, MO highlights the importance of health information technology in the health center context, and illustrates the importance of secure electronic health information systems as a crucial element of disaster and business continuity planning. This article examines the experience of a community health center in the aftermath of the major tornado that swept through the American Midwest in the spring of 2011, and provides insight into the planning for disaster survival and recovery as it relates to patient records and health center data.